Moving Binary-Color Heterojunction for Spatiotemporal Multilevel Encryption via Directional Swelling and Anion Exchange - Liu, Yang; Zhang, Yong (ACS nano, 2021)
Naked-eye-visible color/graphical patterns have shown significant potential in optical encryption. However, current strategies for optical encryption are usually based on static or homogeneous information, which limits their applications in multivalue coding and advanced confidential encryption. Here, we propose a concept of spatiotemporally tunable optical encryption by constructing a multilevel binary-color spatial heterojunction pattern into the time dimension. This multiple coding strategy can enable a simple pattern much more difficult to be counterfeited and keep the facile authentication by naked eyes or smartphone at the same time. As a proof of concept, we fabricated a moving red-green heterojunction pattern by elaborately utilizing the directional swelling process of a poly(dimethylsiloxane) matrix in organic solvents and the ion-exchange property of a perovskite quantum dot wrapped in it. We demonstrate that trioctylphosphine plays a significant role in endowing the red-green heterojunction with a stable and distinct interface for better perception by eyes. The directional swelling and following ion-exchange dynamics in the local interface indicate that we can tailor the movement of the binary-color heterojunction in a quasi-continuous way via orthogonal variables of swelling ratio and ion concentration gradient. The concept of heterojunction-based multivalue optical encryption in the time dimension is independent with other dimensions, indicating a promising compatibility with the existing optical encryption systems.